Pergeseran Partisipasi Sosial (Masyarakat) dalam Masa Pandemi COVID-19 (Tinjauan Fenomenologis Individu Selama Pandemi COVID-19) - Kurniawan, Ignasius Putra (Department of Pancasila and Civic Education, Universitas Negeri Medan, 2022)
AbstractIn this study, my research theme focuses on the phenomenon of Indonesian individual social involvement in responding to the reality of the COVID-19 pandemic. If in normal situations, individual involvement in society looks active. The encounter between individuals becomes a tangible form of the involvement and presence of individuals in society. The focus of this study is to look at the different meanings of the presence and involvement of individuals in society during a pandemic. Each individual can participate in society through their ways. This research study uses a literature methodology. This method is carried out by exploring the phenomena that occur in the community during this pandemic. The finding in this study is the phenomenon of the presence of individuals in a limited society. Limited encounters between individuals remain a form of social engagement but in a different way. Thus, the term